INVESTIGASI EKSTRAK KULIT BATANG KAPUK SEBAGAI INHIBITOR KOROSI PADA BESI ASTM A36 DALAM LARUTAN NaCl 5% - Syarif Hidayatullah; Suteja (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2025)
The growing concern for sustainability and environmental issues in the field of metal corrosion has become increasingly urgent in response to global demands for the adoption of environmentally friendly technologies. One of the widely used approaches to address this challenge is the utilization of plant-based corrosion inhibitors due to their abundant availability and relatively simple extraction process. This study aims to investigate the effect of varying concentrations of kapok bark extract inhibitors specifically at 1000, 2000, and 3000 mg/L on the corrosion rate of ASTM A36 steel in a 5% NaCl solution. The anticorrosion performance and inhibition mechanism were carefully examined through potentiodynamic polarization (PDP) testing and electrochemical impedance spectroscopy (EIS). The results revealed that at a concentration of 3000 mg/L, the kapok bark extract was able to significantly reduce both cathodic and anodic reaction rates. This condition led to a decrease in the corrosion rate from 1.51 to 0.28 mm/year in the NaCl solution. The highest inhibition efficiency, 81.61%, was achieved at an inhibitor concentration of 3000 mg/L. Based on these findings, the kapok bark extract demonstrates significant potential as an environmentally friendly corrosion inhibitor for ASTM A36 steel.